2006
DOI: 10.4321/s1130-01082006000500007
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide for ulcerative colitis

Abstract: In this review, we examined studies published on oral and topical formulations of budesonide (Entocort ® and Budenofalk ® , in Spain: Entocord ® and Intestifalk ® ) for the treatment of ulcerative colitis. This glycocorticosteroid has a potent local action and an important first-pass liver metabolism. It has proven successful over the last years as a controlled-release formulation. It obtained results similar to prednisolone, without the latter's significant suppression of plasma cortisol. Many publications ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Evidence suggests that topical budesonide does not accumulate in the body and compared with other corticosteroids, reaches more central parts of the colon and shows less suppression of plasma cortisol, without diminished efficacy. (48) A study comparing oral budesonide and prednisone showed similar efficacy rates in active and extensive UC. (49) A Cochrane review of budesonide in CD suggested that it may have lower short-term efficacy than other corticosteroids but fewer adverse events.…”
Section: Medical Management In Elderly Ibd Patientsmentioning
confidence: 99%
“…Evidence suggests that topical budesonide does not accumulate in the body and compared with other corticosteroids, reaches more central parts of the colon and shows less suppression of plasma cortisol, without diminished efficacy. (48) A study comparing oral budesonide and prednisone showed similar efficacy rates in active and extensive UC. (49) A Cochrane review of budesonide in CD suggested that it may have lower short-term efficacy than other corticosteroids but fewer adverse events.…”
Section: Medical Management In Elderly Ibd Patientsmentioning
confidence: 99%
“…The first trial published about the use of oral budesonide in CD patients was performed by Lofberg et al in 1993 12. Budesonide is available in three oral dose forms (Table 1): a controlled ileal release form, a pH-dependent release formulation, and a MMX formulation 8,13…”
Section: Pharmacologymentioning
confidence: 99%
“…A pH-dependent release formulation (Budenofalk®, Dr Falk Pharma, Freiburg, Germany) is an enteric coated locally acting glucocorticoid preparation whose pH- and time-dependent coating enables its release into the ileum and ascending colon. This oral formulation consists of a capsule containing L, S, LS, and RS Eudragit® granules that dissolve at pH values above 6.4 13,14…”
Section: Pharmacologymentioning
confidence: 99%
“…These advantages made this drug a standard drug for the localized treatment of inflammatory bowel disease (1,2). BUD is currently marketed in several different commercial forms, as oral controlled-ileal-release formulations targeted at the distal ileum and right-sided colonic region in Crohn's disease, or as enema for the treatment of left-sided ulcerative colitis (UC) (3). However, no BUD formulation is available for the oral treatment of UC (3).…”
mentioning
confidence: 99%
“…BUD is currently marketed in several different commercial forms, as oral controlled-ileal-release formulations targeted at the distal ileum and right-sided colonic region in Crohn's disease, or as enema for the treatment of left-sided ulcerative colitis (UC) (3). However, no BUD formulation is available for the oral treatment of UC (3). It seems that rapid presystemic elimination of BUD in hepatocytes and in epithelial cells of the small intestine wall prevents sufficient bioavailability in colonic mucosa (4,5).…”
mentioning
confidence: 99%